Gambaran Motivasi Belajar Mahasiswa PSIK UGM terhadap Penerapan Flipped Classroom dalam Pembelajaran Keterampilan Klinik Keperawatan - Rizki Salma Fauziah; Totok Harjanto; Kurnia Putri Yuliandari (PSIK FKKMK UGM, 2022)
Background: Flipped Classroom is a learning approach by delivering study content outside the classroom and then followed by instructor-facilitated classroom activities. There are not any research about motivation in clinical skills learning for higher education student.Objective: To describe the student's learning motivation in the flipped classroom strategy for studying nursing clinical skills.Method: This was quantitative descriptive research with cross-sectional design. The sample was taken using a total sampling technique which involved 101 first year students. Data was gathered with the Motivated Strategies for Learning Questionnaire (MSLQ) instrument, which had been tested for validity using Aiken's V (Content Validity Coefficient) with a value range of 0,67-1 for each item and reliability test using Cronbach alpha with a result of 0.964.Result: There were 22 students (21,8%) who achieved high learning motivation, 53 students (52,5%) with moderate learning motivation, and 26 students (25,7%) with low learning motivation. Most students had moderate learning motivation for all six sub-scales.Conclusion: The majority of students have moderate learning motivation in flipped classroom learning. ABSTRAKLatar belakang: Flipped Classroom yaitu pendekatan pembelajaran yang dilakukan dengan mengalihkan penyampaian konten pembelajaran ke luar kelas, kemudian diikuti dengan aktivitas pembelajaran dalam kelas yang difasilitasi oleh instruktur. Belum ada penelitian mengenai motivasi belajar mahasiswa dalam pembelajaran keterampilan klinik. Tujuan: Untuk mengukur motivasi belajar mahasiswa dalam mengikuti pembelajaran keterampilan klinik keperawatan dengan metode flipped classroom.Metode: Jenis penelitian ini yaitu cross-sectional deskriptif kuantitatif. Sampel diambil dengan teknik total sampling dan melibatkan 101 mahasiswa tahun pertama dengan instrumen Motivated Strategies for Learning Questionnaire (MSLQ) yang telah diuji validitas menggunakan Aiken’s V (Content Validity Coefficient) dengan rentang nilai setiap unit 0,67-1 dan uji reliabilitas menggunakan Cronbach alpha dengan hasil 0,964.Hasil: Terdapat 22 mahasiswa yang memiliki motivasi belajar tinggi (21,8%), 53 mahasiswa memiliki motivasi belajar sedang (52,5%), dan 26 mahasiswa memiliki motivasi belajar rendah (25,7%). Mayoritas mahasiswa mempunyai motivasi belajar sedang pada enam sub-skala.Simpulan: Mayoritas mahasiswa mempunyai motivasi belajar tingkat sedang dalam pembelajaran flipped classroom.